2003
DOI: 10.1074/jbc.m308643200
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Accumulation and Swelling in Endosomes Enhances DNA Transfer by Polyamine-DNA Polyplexes

Abstract: The "proton sponge hypothesis" postulates enhanced transgene delivery by cationic polymer-DNA complexes (polyplexes) containing H ؉ buffering polyamines by enhanced endosomal Cl ؊ accumulation and osmotic swelling/lysis. To test this hypothesis, we measured endosomal Cl ؊ concentration, pH, and volume after internalization of polyplexes composed of plasmid DNA and polylysine (POL), a non-buffering polyamine, or the strongly buffering polyamines polyethylenimine (PEI) or polyamidoamine (PAM). [Cl ؊ ] and pH wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
769
5
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 977 publications
(807 citation statements)
references
References 26 publications
19
769
5
3
Order By: Relevance
“…That said, the Cl − s do not notably penetrate between the DNA and PEI molecules, even when the complex is exposed to additional salt. Only little Cl − penetration is observed despite the fact that the Cl − concentration used here, 0.27 M, is considerably higher than the experimentally estimated maximum ∼ 0.1 M. 31 In contrast, the full detachment of one of the less protonated PEI25 molecules from the 5xPEI25-DNA complex occurred in our simulations upon addition of salt. However, the detachment is propelled by the positive ion (Na + ) and not the negative ion (Cl − ) entering the complex.…”
contrasting
confidence: 57%
“…That said, the Cl − s do not notably penetrate between the DNA and PEI molecules, even when the complex is exposed to additional salt. Only little Cl − penetration is observed despite the fact that the Cl − concentration used here, 0.27 M, is considerably higher than the experimentally estimated maximum ∼ 0.1 M. 31 In contrast, the full detachment of one of the less protonated PEI25 molecules from the 5xPEI25-DNA complex occurred in our simulations upon addition of salt. However, the detachment is propelled by the positive ion (Na + ) and not the negative ion (Cl − ) entering the complex.…”
contrasting
confidence: 57%
“…152 Evidence for Cl À accumulation and pH decrease induced by PEI and PAM was shown by using Cl À and pH indicators during polyplex uptake in CHO-K1 cells. 153 In this study, an increase in the volume of polyplex-containing vesicles was observed, followed by dissipation of fluorescentlytagged polyplexes, indicative of vesicle swelling and disruption. While the authors suggest that the polyplexes enter 'macropinocytic' endosomes, it is unclear whether these vesicles are indeed macropinosomes, as it has not been established whether these vesicles acidify or associate with vacuolar proton pumps.…”
Section: Endosomolysismentioning
confidence: 51%
“…12,32 This "proton sponge" mechanism was recently proven by Sonawane et al who showed that endosomes containing vectors with physiologically titratable amine groups like those formed from PEI but not vectors lacking these groups like vectors formed from polylysine buffered H + ions, increased the counterion Cl − concentration within the endosome, swelled the endosome in size, and led to lysis of the endosome. 8 This process is shown in Figure 1. The studies mentioned above highlight the importance of polymer structure including physiologically titratable amine groups in polymeric vector construction.…”
Section: Polymer Structure Determines Endosomal Release To Cytoplasmmentioning
confidence: 99%